The postural stability of children with foetal alcohol spectrum disorders during one-leg stance: A feasibility study - Brink, Yolandi (Afr J Disabil, 2018)
BACKGROUND: Postural control may be impaired in children with foetal alcohol spectrum disorders (FASD). The study assessed the protocol feasibility in terms of (1) recruiting children with FASD in a rural, small town; (2) using the measurement instruments in a real-life setting; (3) the one-leg standing (OLS) task and (4) presenting preliminary results on postural stability of children with and without FASD. METHODS: Nine-year-old children diagnosed with and without FASD were invited to participate. Twenty-eight children performed OLS. Feasibility outcomes included recruitment, measurement instrument use and task instruction. Postural stability outcomes included standing duration, centre of pressure (COP) and body segment acceleration. RESULTS: Participants recruitment was feasible in terms of the (1) ability to sample a reasonable participant number in a rural town setting and the capacity to increase the sample size if more schools are included in the sampling frame and (2) use of assent and consent forms that were appropriate for this population. The measurement instruments were user-friendly, cost-effective and time-efficient. Instructions for the task require amendment to address foot placement of the non-weight–bearing leg. There was a significant difference between cases and controls on mean COP velocity (p = 0.001) and the pelvis segment acceleration in the mediolateral direction (p = 0.01) and the anteroposterior direction (p = 0.027). The control children took longer to achieve postural control. The girls demonstrated a significant difference for the COP anteroposterior displacement (p = 0.008) and velocity (p = 0.049). CONCLUSIONS: The recruitment of children with and without FASD in a rural, small town and the administration of measurement instruments in a real-life, school-based setting was feasible. However, the verbal instructions for the task require revision. The male control group took longer to achieve postural control because the task was performed differently between the two groups. However, the case girls were slower to achieve postural control than control girls though performing the task similarly.